Comparative study of Griseofulvin versus Terbinafine in treatment of Tinea Corporis patients - K Vijaya Chandra Reddy; Somnath Motgi (MRIMS Journal of Health Sciences, 2016)
Background: Dermatophytosis is a superficial infection of keratinized tissue. It is the most common type of cutaneous fungal infection seen in human beings affecting skin, hair and nails. Tinea corporis is one of the most common clinical forms of dermatophytosis. Objective: To compare two oral antifungal drugs, Griseofulvin and Terbinafine in the treatment of Tinea corporis Methods: This is an open-label, randomized, parallel, comparative study which was carried out in 100. Patients with tinea corporis infection who attended the outpatient Department of Dermatology, Dr. PSIMS & RF, Chinaoutpalli, Krishna (Dist), between October 2009 and Aug 2011. This study was approved by the institutional Ethical Committee of Dr. PSIMS & RF. Written consent was taken from all the patients enrolled in the study. Results: tinea corporis in the present study was more common between 18-45 yrs of age group and it is more common in females. In the Griseofulvin group, I patient showed no clinical improvement, 13 showed partial improvement and 32 patients (69.57%) were completely cured. In the Terbinafine group, 5 patients showed partial improvement and 43 patients (89.58%) were completely cured by the end of 4th week. Conclusion: Terbinafine 250 mg tablet taken once daily for 2 weeks is more effective in complete cure (both clinical and mycological cure) and showed an early clinical response in treatment of tinea corporis compared to Griseofulvin 250 mg tablet taken twice daily for 4 weeks. There was no significant difference between the two drugs regarding tolerability.